Determination of methods for achieving the surprise of the actions of the National Guard of Ukraine in a special operation for neutralizing illegal armed formations - Kolyanda, V. V.; Drobakha G. А.; Adamchuk М. М. (Honor and Law, 2019)
Based on the analysis of combat experience, methods have been developed for achieving the suddenness of the actions of the National Guard of Ukraine formations in a special operation on the neutralization of illegal armed formation, their ranking and identification of the most significant ones.